Smart bus terminal using infrared identification - Mohamed Zahir, Mohd Akram Zaki; Md Yunos, Yusri; Mazumi, Mazhaniza; Wahap, Ahmad Ridhwan; Wahid, Herman; Ahmad, Anita; Ramli, Mimi Faisyalini; Mohd Zain, Rasif (Penerbit UTHM, 2022)
Significant increase in vehicles inside city areas results in adding more troubles to that section of citizens using public transportation network as their primary source of travelling. This specific section of society is a victim of this rapid growing traffic volume and causing a huge waste of time due to not having proper information of required bus current position. The problem results in not only wasting of time but also mentally unhappy and tensed citizens. Nowadays, passengers want to get the clear information of their desired buses at station, like the position and estimated time of arrival of bus etc. The implementation of Intelligent Transportation Systems (ITS) nowadays has developed to the incredible extent. This system is proved that is to be very useful not only in the safety purpose but also it eases to any users. The combination with infrared can use to monitor and identify the location of certain bus and present it the information to the bus passenger on LCD at terminal by using the simulation. The tag and the reader of the infrared devices are wirelessly connected and control station can authorize not only to monitor the bus but can also identify the particular of the bus such as bus registration number and bus company names.